Making the invisible visible: observing the UV-reversal effect in quartz using radiofluorescence - Friedrich, Johannes; Kreutzer, Sebastian; Schmidt, Christoph (Journal of physics. D, Applied physics, 2018)
The pre-dose effect is one of the most well-known phenomena in quartz luminescence. It refers to an increase in dose sensitivity subsequent to radiation pre-exposure and annealing. A theoretical description of this phenomenon exists since the 1970s and is widely used in recent luminescence models. However, also the opposite effect has been described, the less known ‘UV-reversal’ effect which reduces the luminescence sensitivity due to illuminating the sample with far UV light. Both effects were detected with thermoluminescence (TL) following a small test dose and observing the effect indirectly using the response of the 110 °C peak. We here present a more direct measurement of both phenomena via UV-radiofluorescence (UV-RF), which is the luminescence emitted during irradiation. Therefore, the need of a TL measurement is obsolete. Furthermore, we were able to calculate a time rate of eviction of holes from the luminescence centre and implement this value into existing models to obtain a more comprehensive description of quartz luminescence. Numerical simulations are in good agreement with experimental data.